Distinct Functions of the Primate Putamen Direct and Indirect Pathways in Adaptive Outcome-Based Action Selection - Ueda, Yasumasa; Yamanaka, Ko; Noritake, Atsushi; Enomoto, Kazuki; Matsumoto, Naoyuki; Yamada, Hiroshi; Samejima, Kazuyuki; Inokawa, Hitoshi; Hori, Yukiko; Nakamura, Kae; Kimura, Minoru (Frontiers in Neuroanatomy, 2017)
Cortico-basal ganglia circuits are critical regulators of reward-based decision making. Reinforcement learning models posit that action reward value is encoded by the firing activity of striatal medium spiny neurons and updated upon changing reinforcement contingencies by dopamine signaling to these neurons. However, it remains unclear how the anatomically distinct direct and indirect pathways through the basal ganglia are involved in updating action reward value under changing contingencies. Medium spiny neurons of the direct pathway predominantly express dopamine D1 receptors and those of the indirect pathway predominantly D2 receptors, so we tested for distinct functions in behavioral adaptation by injecting D1 and D2 receptor antagonists into the putamen of two macaque monkeys performing a free choice task for probabilistic reward. In this task, monkeys turned a handle toward either a left or right target depending on an asymmetrically assigned probability of large reward. Reward probabilities of left and right targets changed after 30–150 trials, so the monkeys were required to learn the higher-value target choice based on action−outcome history. In the control condition, the monkeys showed stable selection of the higher-value target (that more likely to yield large reward) and kept choosing the higher-value target regardless of less frequent small reward outcomes. The monkeys also made flexible changes of selection away from the high-value target when two or three small reward outcomes occurred randomly in succession. Dopamine D1 antagonist injection significantly increased the probability of the monkey switching to the alternate target in response to successive small reward outcomes. Conversely, D2 antagonist injection significantly decreased the switching probability. These results suggest distinct functions of D1 and D2 receptor-mediated signaling processes in action selection based on action−outcome history, with D1 receptor-mediated signaling promoting the stable choice of higher-value targets and D2 receptor-mediated signaling promoting a switch in action away from small reward outcomes. Therefore, direct and indirect pathways appear to have complementary functions in maintaining optimal goal-directed action selection and updating action value, which are dependent on D1 and D2 dopamine receptor signaling.